Parents' Motivation in Choosing Islamic Boarding Schools as Educational Institutions for Their Children in a Muslim Majority Country - Parta, Muhammad Hakim; Mulyadi, Ilham (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
Continuing children's education is a responsibility of every parent, including choosing the right educational institution, one of which is an Islamic boarding school. This study aims to identify the motivations of parents and children in choosing an Islamic boarding school as an educational institution. This research employs a qualitative method with a case study approach. Data were obtained from eight informants through direct interviews using a set of interview protocols. Overall, the results revealed seven main themes regarding parents’ and children’s motivations in choosing Islamic boarding schools as educational institutions. These themes are divided into three parental motivation themes and four child motivation themes. The three parental motivations are: i) strengthening the child’s religious foundation, ii) avoiding negative social influences, and iii) the desire to shape the child into a better person. Furthermore, the four themes of children’s motivation are: i) self-initiative, ii) parental encouragement, iii) deepening religious knowledge, and iv) the aspiration to become a hafidz or hafidzah. The findings of this study suggest that effective communication and value alignment between parents and children may play an important role in decision-making regarding faith-based education.